Legal Analysis of Balanced Housing Using the Land Banking System in Jakarta - Hillary Hendry; Rasji Rasji (Eduvest - Journal of Universal Studies, 2024)
In the application, there are several inhibiting factors in applying this balanced residential concept, including relat-ed to the lack of land availability so that the price of availa-ble land becomes expensive and currently not many develop-ers are applying the concept of balanced residential, especial-ly in the Jakarta area. In a housing area, it is definitely de-termined by the price of land in addition to the location, in-cluding the completeness of facilities in the housing area. Land prices in Jakarta city centers are already relatively high so that many developers only build expensive housing for the upper middle class. To prevent this, the government created the Land Bank concept. The main purpose of Land Banking is to acquire land which is then used for the benefit of the welfare of the community, especially in meeting the needs of a house. However, in practice, the Land Bank Concept is still not widely recognized in the wider community, especially housing developers, so there are still few developers who ap-ply the Balanced Residential Concept using the Land Bank System, especially in Jakarta because the rules and regula-tions of the Land Bank System are relatively new. And if people want to sell or buy a land or residential land then they will look for services in brokers or property developers only.